2015
DOI: 10.1186/s12885-015-1804-x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience with home-based self-sampling for human papillomavirus testing

Abstract: BackgroundIncreasing cervical screening coverage by reaching inadequately screened groups is essential for improving the effectiveness of cervical screening programs. Offering HPV self-sampling to women who are never or under-screened can improve screening participation, however participation varies widely between settings. Information on women’s experience with self-sampling and preferences for future self-sampling screening is essential for programs to optimize participation.MethodsThe survey was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
107
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 16 publications
21
107
4
Order By: Relevance
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
“…Most previous studies have also reported that a majority of participating women preferred self-sampling [6, 8, 24, 25, 27, 29, 30, 31, 35, 36, 37, 38], although some have returned the opposite finding [26, 28, 34, 39]. In our study, a higher proportion of women who were not adherent to Pap screening, relative to adherent women, preferred self-testing over clinician testing.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Self-collected cervical samples receiving hpv testing show comparable cin2+ sensitivity compared with clinician-collected samples tested with cytology and with hpv 10-12 . Self-collection has proven to be highly acceptable among women 13 .…”
Section: Paradigm Shift Towards Hpv Screening Globallymentioning
confidence: 99%
“…Some women, particularly those who have experienced abuse 14 or are otherwise marginalized, may find self-sampling preferable because of such things as cultural/religious embarrassment or discomfort associated with a pelvic exam 13,[15][16][17] . Time, transportation, inconvenient clinic hours, or not having a regular practitioner are also relevant factors associated with under-screening that can be mitigated through hpv self-collection using mailed samples 13,16,17 . However, there are psychosocial barriers to hpv screening, including women's lack of awareness and fears around hpv and cervical cancer screening, which cannot be addressed through self-collection-based screening alone 17,18 .…”
Section: Paradigm Shift Towards Hpv Screening Globallymentioning
confidence: 99%